PENGARUH COVID-19 TERHADAP HARGA SAHAM DI INDONESIA TAHUN 2019-2020 - Shaula Andreinna Arthamevia; Maulidya Ayu; Umniyyatul Ula; Silva Rizqi; Farhatun Nissa; Hendro Cahyo (Seminar Nasional Official Statistics, 2020)
Stock is a capital market instrument that can be defined as a sign of individual or unilateral capital participation (business entity) in a company or limited liability company. The current factor in the stock market sector is the impact of the corona virus on the stock price index and the flow of foreign funds to the stock market. So it is very necessary to conduct an analysis of the impact of the corona pandemic virus on the stock market sector to see how the JCI movement in Indonesia compares before the pandemic and during the Covid-19 pandemic. The method used for comparative analysis is the Simple Moving Average and the Weighted Moving Average. From the results of descriptive analysis on the JCI data in Indonesia, the average Adj Close variable before the pandemic occurred was 6353.71, with a minimum value of 5907.12 and a maximum value of 6525.36. The average value during the pandemic was 5143,929, with a minimum value of 3937,632 and a maximum value of 6325,406. The comparison results show that the Weighted Moving Average method is used because with the 2019 IHSG MAPE value of 0.844287 the 2020 IHSG MAPE value is 3.489167 which is smaller than the Simple Moving Average method. As well as the results of the comparison of the impact of the JCI from before the pandemic occurred with data where the pandemic was occurring was very influential and the JCI decreased when it was declared that Indonesia was infected with Covid-19.